Informal E-waste Collection Units and Intention of using Technology - P.S., Ms. Anusree; Balasubramanian, Dr. P. (The journal of contemporary issues in business and government, 2021)
Technological advancement and resultant proliferation of electronic dumps has immensely hampered health and environment. Authorities in developed and developing countries, find it difficult to control the exponentially growing e-waste menace and the toxic dangers associated with it. However, internet communications and technologies have transformed the way e-waste management scenario is looked upon. Advanced technologies including cloud computing, Internet of Things and Big Data has created new dimensions in management by opening opportunities that are convenient and easily accessible. These have made management activities including collection, transportation, recycling and reuse of electronic equipments with stakeholders much easier. This paper utilized behavioral scales in analyzing the perspective of informal e-waste colleciton units in using technology forcollection activities.